The Effect of Progressive Muscle Relaxation with Self Instruction Training (SIT) Techniques in Video Media on The Sleep Quality of Hemodialysis Patients - Dhian Luluh Rohmawati; Endri Ekayamti; Sandy Wahyu Pratama; Asrina Pitayanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Chronic kidney disease (CKD) is a global public health problem whose prevalence continues to increase every year. CKD is when the kidneys experience structural and functional disorders lasting over 3 months. Sleep disorders generally occur in people with chronic kidney disease, especially in people with end-stage kidney disease. Progressive muscle relaxation is one of the complementary therapies that can reduce anxiety, reduce pain, and lower muscle tension. Objectives: The aims of this research is to analyze the effect of progressive muscle relacxation with self instruction training (SIT) Technique in Video Media on The Sleep Quality of Hemodialysis Patients. Methods: The research design used was Pre-Eksperimental using a one-group pre-post test with a sample of 15 hemodialysis patients by purposive sampling. Results: The results showed that the quality of sleep before progressive muscle relaxation was 11 respondents (73.3%) whose frequency of sleep quality was quite poor. After progressive muscle relaxation, 8 respondents (53.3%) had a fairly good frequency of sleep quality. The results of statistical tests using the Wilcoxon test showed there was a significant influence between progressive muscle relaxation on sleep quality in hemodialysis patients (p-value=0.002). Conclusions: Progressive muscle relaxation plays a role in relaxing tense muscles and providing a sense of comfort and has an impact on improving sleep quality. Progressive muscle relaxation can be used as an alternative in improving sleep quality in hemodialysis patients.